Futuristic technology perspectives on entrepreneurship and sustainable innovation - Misra, Sanjay 1971-; Jain, Amit 1978-; Kaushik, Manju; Banerjee, Chitreshh (Advances in IT personnel and project management (AITPPM) book series, 2023)
Entrepreneurs and information technology have formed the backbone of the global economy, as seen by the description presented. The growing use of information technology in society and most industries/businesses, as well as the economic convergence of entrepreneurship and innovation, highlight the need for a leading and authoritative research handbook to disseminate cutting-edge findings on entrepreneurship and innovation in the context of IT from an international perspective. The proposed book will provide academics, entrepreneurs, managers, and practitioners with up-to-date, comprehensive, and rigorous research-based articles on the formation and implementation of effective strategies and business plans, as well as current studies on the nature, process, and practice of entrepreneurship and innovation in the development, implementation, and application of information technology worldwide.